Cryptic lineage diversity, body size divergence, and sympatry in a species complex of Australian lizards (Gehyra). (1st January 2018) - Moritz, Craig C.; Pratt, Renae C.; Bank, Sarah; Bourke, Gayleen; Bragg, Jason G.; Doughty, Paul; Keogh, J. Scott; Laver, Rebecca J.; Potter, Sally; Teasdale, Luisa C.; Tedeschi, Leonardo G.; Oliver, Paul M.
Abstract: Understanding the joint evolutionary and ecological underpinnings of sympatry among close relatives remains a key challenge in biology. This problem can be addressed through joint phylogenomic and phenotypic analysis of complexes of closely related lineages within, and across, species and hence representing the speciation continuum. For a complex of tropical geckos from northern Australia— Gehyra nana and close relatives—we combine mtDNA phylogeography, exon‐capture sequencing, and morphological data to resolve independently evolving lineages and infer their divergence history and patterns of morphological evolution. Gehyra nana is found to include nine divergent lineages and is paraphyletic with four other species from the Kimberley region of north‐west Australia. Across these 13 taxa, 12 of which are restricted to rocky habitats, several lineages overlap geographically, including on the diverse Kimberley islands. Morphological evolution is dominated by body size shifts, and both body size and shape have evolved gradually across the group. However, larger body size shifts are observed among overlapping taxa than among closely related parapatric lineages of G. nana, and sympatric lineages are more divergent than expected at random. Whether elevated body size differences among sympatric lineages are due to ecological sorting or character displacement remains to be determined.